Platelet glycoprotein GP VI 13254C allele is an independent risk factor of premature myocardial infarction - Motovska, Zuzana; Kvasnicka, Jan; Widimsky, Petr; Petr, Robert; Hajkova, Jaroslava; Bobcikova, Petra; Osmancik, Pavel; Odvodyova, Denisa; Katina, Stanislav (Thrombosis research, 2010)
AIM: The purpose of this study was to asses the impact of haemostatic and platelet receptor gene polymorphisms as an inherited risk factor for premature onset of myocardial infarction (MI). METHODS: Polymorphisms of platelet receptors - GP Ia (807C>T, rs1126643), GP VI (13254T>C, rs1613662), GP IIIa (HPA-1, rs5918), PAR -1 (IVS -14A>T; rs168753), P2Y(12) (34C>T, rs6785930 and H1/H2 haplotype, rs2046934), and genetic variations of the gene coding for cyclooxygenase-1 (COX-1) ( -842A>G, rs10306114 and 50C>T, rs3842787) were investigated. Mutations in the genes coding for coagulation factor V (Q506R (Leiden) mutation, rs6025) and factor II (prothrombin G20210A, rs1799963) were also determined. The prevalence of gene polymorphisms was investigated in 105 consecutive patients with premature MI. This was compared with the same gene polymorphism prevalence in a group of 132 patients in which coronary artery disease had been excluded. Genotyping was done using PCR, followed by melting curve analysis with specific fluorescent hybridization probes. RESULTS: A significant association between GP VI 13254C allele carriers and premature MI was found (p=0.025). No other differences in prevalence of the investigated polymorphisms between the compared patient populations reached statistical significance. In a logistic regression, which took other cardiovascular risk factors into account, the significance of the GP VI 13254C allele and vascular risk was suggested (OR 1.888, 95% C.I. 1.029 to 3.464, p=0.040). In a binary logistic regression the positive relationship between the GP VI genotype and female gender was observed (0R 3.676; 95% C.I. 1.159 to 11.628; p=0.027). The frequencies of GP VI and GP Ia gene polymorphisms were independent of one another (p=0.836). CONCLUSION: The presence of the GP VI 13254C allele is an independent predictor of premature MI.
Keywords: alely; Alleles; Adult; Male; lidé; Genotype; lidé středního věku; Humans; Randomized Controlled Trials as Topic; randomizované kontrolované studie jako téma; Middle Aged; infarkt myokardu; Gene Frequency; Polymorphism, Genetic; frekvence genu; Myocardial Infarction; logistické modely; Logistic Models; Platelet Membrane Glycoproteins; rizikové faktory; mužské pohlaví; polymorfismus genetický; dospělí; ženské pohlaví; genotyp; Female; Risk Factors; glykoproteiny membrány trombocytů